2023
DOI: 10.1007/s00421-022-05128-6
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced skeletal muscle angiogenesis: impact of age, sex, angiocrines and cellular mediators

Abstract: Exercise-induced skeletal muscle angiogenesis is a well-known physiological adaptation that occurs in humans in response to exercise training and can lead to endurance performance benefits, as well as improvements in cardiovascular and skeletal tissue health. An increase in capillary density in skeletal muscle improves diffusive oxygen exchange and waste extraction, and thus greater fatigue resistance, which has application to athletes but also to the general population. Exercise-induced angiogenesis can signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 215 publications
0
15
0
Order By: Relevance
“…Furthermore, the exact link between CD300LG and glucose metabolism is not clear, but possibly related to the fact that CD300LG is expressed in endothelial cells 54 , linked to blood pressure 55 , lymphocyte binding 56 , blood triacylglycerol levels 57,58 and molecular traffic across the capillary endothelium 59 . Both MyoGlu and GD-CAT data also suggested that CD300LG may be related to angiogenesis in ScWAT 60 and SkM 60,61 , at least in men. Hence, we speculate that the link between CD300LG and glucose metabolism is related to improved tissue capillarization/vascular function following prolonged exercise.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the exact link between CD300LG and glucose metabolism is not clear, but possibly related to the fact that CD300LG is expressed in endothelial cells 54 , linked to blood pressure 55 , lymphocyte binding 56 , blood triacylglycerol levels 57,58 and molecular traffic across the capillary endothelium 59 . Both MyoGlu and GD-CAT data also suggested that CD300LG may be related to angiogenesis in ScWAT 60 and SkM 60,61 , at least in men. Hence, we speculate that the link between CD300LG and glucose metabolism is related to improved tissue capillarization/vascular function following prolonged exercise.…”
Section: Discussionmentioning
confidence: 91%
“…Usually, a personalized session duration and intensity are required. They are particularly important because they allow an adaptation of the patient for the energy requests and the oxygen consumption and a modification of muscle structure and function, which are fundamental for endurance [ 51 ]. Among the exercises, specific protocols exist for entrapment neuropathies.…”
Section: Discussionmentioning
confidence: 99%
“…PGC1-α has also been reported to mediate exercise-induced angiogenesis, possibly via angiogenic-regulating factors like vascular endothelial growth factor (VEGF) [99,100,[104][105][106]. Exercise-induced skeletal muscle angiogenesis is a well-known physiological adaptation to exercise and may thereby lead to improved endurance performance capacity and cardiovascular function [104,107]. Moreover, fucoxanthin has been reported to increase Kelch-like ECH-associated protein 1 (KEAP 1 )-NRF 2 pathway activity, which participates in regulating angiogenesis and mitochondrial biogenesis with positive interactions with the PGC1-α pathway [105,108,109].…”
Section: Secondary Outcomesmentioning
confidence: 99%